Multidisciplinary lines of evidence reveal East/Northeast Asian origins of agriculturalist/pastoralist residents at a Han dynasty military outpost in ancient Xinjiang - Allen, Edward; Yu, Yao; Yang, Xiaomin; Xu, Yiran; Du, Panxin; Xiong, Jianxue; Chen, Dian; Tian, Xiaohong; Wu, Yong; Qin, Xiaoli; Sheng, Pengfei; Wang, Chuan-Chao; et al. (Frontiers in Ecology and Evolution, 2022)
Han/non-Han interactions were engrained among the border regions of ancient Imperial China. Yet precious little is known on either the genetic origins or the lifeways of these border peoples. Our study applies tools from ancient DNA and stable isotope analysis to the study of a Han dynasty population at the Shichengzi site in modern-day Xinjiang. Isotopic analysis (δ13C and δ15N) of human (n = 8), animal (n = 26), and crop remains (n = 23) from Shichengzi indicated that dietary patterns among site inhabitants could be split among agro-pastoral and agricultural groups based on differences in the collagen 15N ratios. DNA analysis divided the four Shichengzi samples into two groups, with one group primarily harboring ancient Northeast Asian (ANA) related ancestry, while the other showed a dominant Late Neolithic Yellow River (YR_LN) related ancestry. Both ancient DNA and stable isotope evidence point to the Northeast Asian origins of pastoralists and East Asian origins of Han agriculturalists, who nonetheless shared a single burial space at Shichengzi. This study thus provides clear evidence for the multiple origins and identities of populations across the porous border represented by the Han Empire and surrounding regions and proposes a new model for the interpretation of border culture in early Imperial China.